The association of dietary insulinemic indices with PI3K, PTEN, and Akt gene expressions in visceral and subcutaneous adipose tissues among individuals undergoing abdominal surgery - Ahmadirad, Hamid; Teymoori, Farshad; Farhadnejad, Hossein; Shimi, Ghazaleh; Asghari, Golaleh; Yuzbashian, Emad; Zarkesh, Maryam; Mirmiran, Parvin; Khalaj, Alireza (Frontiers in Nutrition, 2024)
Background/Objective: The current study investigates the association between dietary insulinemic indices and Akt, PTEN, and PI3K gene expressions in visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) among individuals undergoing abdominal surgery. Material and Methods: This cross-sectional study was conducted on 176 individuals, aged 18-84 years, who had undergone abdominal surgery. The participants were classified based on body mass index(BMI) as normal(BMI<25 kg/m2 ), overweight(BMI=25-29.9 kg/m 2 ), and obese(BMI≥30 kg/m 2 ). The food frequency questionnaire was used to determine dietary glycemic and insulinemic indices. Real-time polymerase chain reaction was conducted for expression of PI3K, PTEN, and Akt genes. Results: In the final adjusted model, in normal-weight patients, there was an inverse relationship between the lifestyle with a higher insulinemic potential and the PI3K gene expression in VAT. Also, there was an inverse association between dietary insulin load and the Akt gene expression in VAT. However, a higher glycemic index was positively associated with the PTEN gene expression in VAT. In overweight patients, a high insulinemic potential of the diet was associated with higher PTEN gene expression in VAT. In obese individuals, there were positive associations between lifestyle index for insulin resistance and hyperinsulinemia and the PI3K gene expression in VAT. Moreover, the higher insulinemic potential of diet and lifestyle was positively related to a higher expression of the PTEN and Akt genes in VAT. Conclusions: Our findings revealed that high insulinemic lifestyles and dietary patterns may be related to the expression of PI3K, PTEN, and Akt in adipose tissues.